2013
DOI: 10.1148/radiol.13120733
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Review of the Temporal Bone: Part I. Anatomy and Inflammatory and Neoplastic Processes

Abstract: From a clinical-radiologic standpoint, there are a limited number of structures and disease entities in the temporal bone with which one must be familiar in order to proficiently interpret a computed tomographic or magnetic resonance imaging study of the temporal bone. It is helpful to examine the region in an organized and systematic fashion, going through the same checklist of key structures each time. This is the first of a two-part review that provides a practical approach to understanding temporal bone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 81 publications
1
116
0
7
Order By: Relevance
“…glomus tumor (most common), facial nerve schwannomas and geniculate region hemangiomas extending to middle ear, choristomas, and malignancies such as carcinomas and metastases (rare). 13 In the current CT scan study, three of the six tumors observed were glomus tympanicum tumors, more commonly in female patients than male (2:1), in line with literature. 10 The other tumors observed in this study were middle ear malignancy and EAC malignancy.…”
Section: Discussionsupporting
confidence: 89%
“…glomus tumor (most common), facial nerve schwannomas and geniculate region hemangiomas extending to middle ear, choristomas, and malignancies such as carcinomas and metastases (rare). 13 In the current CT scan study, three of the six tumors observed were glomus tympanicum tumors, more commonly in female patients than male (2:1), in line with literature. 10 The other tumors observed in this study were middle ear malignancy and EAC malignancy.…”
Section: Discussionsupporting
confidence: 89%
“…After the scan was taken, radiologist gave the detailed reporting of the temporal bone. 4 All the patients went through ear surgery and all the findings seen intra-operatively were noted. Both the radiological and surgical findings were tabulated and correlated with each other.…”
Section: Scanning Parametersmentioning
confidence: 99%
“…A possible resulting subperiosteal abscess may lead to a rare Bezold abscess, where infection extends between the digastric and sternocleidomastoid muscles. 2,8,9 At MRI, AOM presents as tympanic and mastoid high T2-weighted (W) signal material. Contrast-enhanced MRI (CE-MRI) is useful in assessing complications, such as labyrinthitis seen as inner ear contrast-enhancement, dural venous sinus thrombosis with venous filling defects, extra-or intracranial abscess formation with a rim-enhancing collection, or meningitis with leptomeningeal enhancement 5 (Fig 1b).…”
Section: Introductionmentioning
confidence: 99%
“…This may cause deep facial pain with abducens nerve palsy, termed Gradenigo's syndrome, and should not be confused with the asymptomatic finding of trapped residual fluid within the petrous apex air cells. 8,10,11 The differential diagnosis includes cholesteatoma, cholesterol granuloma, and in children, Langerhans' cell histiocytosis (LCH). 2e3,12 However, cholesteatoma and cholesterol granuloma are typically associated with chronic otitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation